2020
DOI: 10.1369/0022155420954296
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan and Its Receptors as Regulatory Molecules of the Endothelial Interface

Abstract: On the surface of endothelial cells (ECs) lies the glycocalyx, a barrier of polysaccharides that isolates the ECs from the blood. The role of the glycocalyx is dynamic and complex, thanks to not only its structure, but its vast number of components, one being hyaluronan (HA). HA is a critical component of the glycocalyx, having been found to have a wide variety of functions depending on its molecular weight, its modification, and receptor–ligand interactions. As HA and viscous blood are in constant contact, HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 91 publications
0
22
1
Order By: Relevance
“…Of particular significance, a substantial portion of this HA occupied the central lumen rather than being restricted only to the luminal surface of the ECs in a classical vascular glycocalyx. 37,38 In contrast to the presence of HA in HUVEC tube lumens, we did not detect HA on the exterior of HUVEC tubes, which may reflect the reported absence of an abluminal polysaccharide layer near the growing tips of neovessels in vivo. 37 The absence of abluminal HA on our HUVEC tubes does not, by itself, indicate a complete absence of an exterior cell coat, as we have previously shown that biglycan is present on the exterior surfaces of these tubes.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Of particular significance, a substantial portion of this HA occupied the central lumen rather than being restricted only to the luminal surface of the ECs in a classical vascular glycocalyx. 37,38 In contrast to the presence of HA in HUVEC tube lumens, we did not detect HA on the exterior of HUVEC tubes, which may reflect the reported absence of an abluminal polysaccharide layer near the growing tips of neovessels in vivo. 37 The absence of abluminal HA on our HUVEC tubes does not, by itself, indicate a complete absence of an exterior cell coat, as we have previously shown that biglycan is present on the exterior surfaces of these tubes.…”
Section: Discussioncontrasting
confidence: 59%
“…At present, the means by which endogenous HA could contribute to lumen development is not clear. Purified o-HA is reported to stimulate EC proliferation, migration, secretion of angiogenic factors, and overall vascular growth via receptor-mediated (e.g., CD44/ RHAMM) signaling, 38,44 although the direct involvement of o-HA in lumen development has not been established. Of note, there are concerns that some of the biological effects of LMW-HA/o-HA (e.g., induction of inflammatory responses) may be the consequence of contamination with endotoxin, 14 which has been shown to elicit proangiogenic behaviors in ECs.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of HA synthesis depends on the availability of substrate sugars (129), and conversely, high rates of HA synthesis are associated with a shift of cellular metabolism to glycolysis (130)(131)(132). HA binds to cell-surface receptors CD44 (133), RHAMM (receptor hyaluronan mediated motility) (134) and the lymphatic EC receptor LYVE-1. The cytoplasmic domain of CD44, a single pass membrane-spanning receptor, is coupled to cortical actin by ERM (ezrin radixin moesin) proteins (135).…”
Section: Hyaluronic Acid/hyaluronanmentioning
confidence: 99%
“…HA polymers are hydrated with 15 H 2 O molecules per disaccharide unit ( 145 ). At the apical/luminal EC surface HA interweaves with other components of the glycocalyx/ESL ( 110 , 134 ) and shear stress ( 129 , 146 ) and inflammatory stimuli ( 147 ) augment HA accumulation in the EC glycocalyx. HA binds proteoglycans in the hyalectin family (see below) forming large, patterned aggregates.…”
Section: Molecular Components Of the Ec Glycocalyxmentioning
confidence: 99%
“…Moving from metabolic regulation of HA on to the function of HA and its receptor, CD44, Queisser, Mellema, and Petrey introduce us to the glycocalyx. 9 This specialized extracellular matrix, rich in HA and other GAGs, is located between blood and the endothelial surface and has critical roles in homeostatic vascular function. In contrast to the role of metabolic flux in regulating HAS activity discussed above, here the authors introduce the role that HA and the proteins to which it binds plays as mechanosensory transducers, transmitting extracellular signals into the cell.…”
mentioning
confidence: 99%